Nursing care in the treatment of breast cancer: a literary review - Gomes, Jislaynne Lins; Freire, Thâmara Tenório; Silva, João Paulo Malta da; Santos, Maísa Isabella Faustino (JRG Journal of Academic Studies, 2023)
Breast cancer is one of the most feared diseases among women in Brazil, characterized by the uncontrolled growth of abnormal cells resulting in both emotional and physical impacts. This condition demands a humanized approach by the healthcare team, with a particular emphasis on the role of nurses in building relationships with their patients. This integrative literature review, conducted in the databases of the Virtual Health Library (BVS/Bireme), LILACS, and MEDLINE/PUBMED, aimed to analyze nursing interventions in the treatment of women with breast cancer, emphasizing the importance of the presence of these professionals during this critical phase. Inclusion criteria encompassed articles published in the last five years in Portuguese and English, with online availability of abstracts and full texts, excluding review articles and those not related to the research question. The literature review revealed that nursing plays a multifaceted role in the care of women with breast cancer. Their activities include exchanging information about the disease and its treatment, providing emotional support, psychological assistance, and humanizing care. These actions are carried out through consultations, home visits, and educational activities, resulting in a significant improvement in the quality of life of patients and a greater acceptance of the disease. Regarding the results and conclusion of this study, it is highlighted that the role of nursing is fundamental for comprehensive care for women with breast cancer. Nurses play an essential role in promoting well-being and acceptance of the disease, contributing to a more positive experience in the treatment process. However, the ongoing pursuit of qualification and professional development is crucial to ensure the delivery of quality care to these patients. In summary, this study emphasizes the importance of nurses in the care of women with breast cancer and underscores the need for continuous improvement to provide humanized and effective assistance.